Ethical Issues In Assisted Reproductive Technologies - Varada Jayant Madge (Social Medicine Publication Group, 2011)
Biomedicine approaches infertility as a disease that can be cured with the application of Assisted Reproductive Technologies (ART). This study aims to explore some of the ethical issues that surround the use of these technologies in India. The study was carried out in two well-known private health care settings in Pune, Maharashtra. One of the private hospitals was selected on the basis of familiarity with the doctor; the other on the basis of popularity among patients. Qualitative in-depth interviews were conducted to collect information from a sample of 25 women between December 2007 and April 2008. The study reveals that all the women interviewed found ART treatment to be painful and-at the time of interview-had not achieved a full-term pregnancy. The study also found that there was no uniform protocol specifying the sequenced application of intrauterine insemination (IUI)followed by the enrolment of the woman in in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). The interviews found that the women were burdened by the treatment. These technologies are based on profit at the cost of women's lives. Literature suggests that there are chances that embryos are made available for research without the consent of couples, and these embryos could be manipulated prior to transfer, thus trying to control birth. Based on the findings from this study and on previous literature (Raymond 1993) these IUI, IVF, and ICSI technologies should not become medical practice, until they have undergone a scientific evaluation. Keywords: IUI, IVF, ICSI, informed consent, painful, burdened, uniform protocol